Strategi Pembelajaran Inovatif untuk Meningkatkan Keterlibatan dan Hasil Belajar Siswa di Era Digital - Irfan Syafei Siregar; Ahmad Dairoby Lubis; Gusmanelli Gusmanelli (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The digital era presents new challenges and opportunities in the world of education. Students now live in the midst of abundant technology and information, so that conventional learning approaches are often no longer relevant. This article aims to examine various innovative learning strategies that can improve student engagement and learning outcomes. With a qualitative approach and literature study, this study found that technology integration, active learning approaches, and the use of digital interactive media can significantly increase student motivation and participation. The implications of these findings suggest that teachers need to design more adaptive and creative learning in facing the challenges of the 21st century.